2001
DOI: 10.1007/s00270-001-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Cerebral Protection with a Filter Device During Stent Implantation of the Carotid Artery

Abstract: Cerebral protection with the filter device is technically feasible in most cases. DW-MRI demonstrated new cerebral lesions indicating the occurrence of cerebral microemboli during the protected procedures. Further investigations are necessary to determine whether the use of the cerebral protection device will improve the results of CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
6

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 17 publications
0
59
0
6
Order By: Relevance
“…Several authors have published their uncontrolled monocenter results mostly comparing older data from unprotected interventions with patient groups in which they used PD. 5,6,[12][13][14][15] Almost all of these studies concluded that PD appear to reduce the thromboembolic complication rate and are strongly recommended in CAS procedures. 5,16 Despite the lack of controlled studies, the use of these devices has or had become obligatory in the ongoing CREST 17 and in the interrupted EVA-3S 18 trials testing whether CAS and CEA are equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have published their uncontrolled monocenter results mostly comparing older data from unprotected interventions with patient groups in which they used PD. 5,6,[12][13][14][15] Almost all of these studies concluded that PD appear to reduce the thromboembolic complication rate and are strongly recommended in CAS procedures. 5,16 Despite the lack of controlled studies, the use of these devices has or had become obligatory in the ongoing CREST 17 and in the interrupted EVA-3S 18 trials testing whether CAS and CEA are equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Nevertheless, embolization of microparticles through pores with a medium size of 100 m is a major drawback commonly detected by intraprocedural transcranial Doppler sonography or as new-onset focal ischemic lesions on DWI after CAS. [5][6][7][8][9][10][11][18][19][20] Some evidence suggests that mostly the size of particles relates to the occurrence of periprocedural symptomatic neurologic events [21][22][23][24] and that the brain demonstrates a good tolerance for ischemia caused by these emboli. However, recent reports stress the role that silent ischemia may play in the genesis and maintenance of neurocognitive disorders in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, although CPDs seem safe and effective, silent ischemic lesions secondary to distal embolization have been depicted on diffusion-weighted imaging (DWI) by several authors. [5][6][7][8][9][10][11] The morphology of the atherosclerotic wall has been the focus of general interest because it has been proved to have a pivotal role in plaque vulnerability. 12 The purposes of our study were to describe the method and results of the morphologic analysis of filter content in protected CAS of severe ICA stenosis and to evaluate any correlation found with demographic characteristics, procedural events, and morbidomortality during and up to 30 days after CAS.…”
mentioning
confidence: 99%
“…Some experts have indicated that the use of these distal protection devices during CAS in general can significantly reduce thromboembolic complication rates 7 and frequency of microembolic signals during TCD monitoring 4 . However, Schluter et Al indicated that neuroprotected CAS is associated in about 25% of cases with predominantly silent cerebral ischemia on postoperative diffusion-weighted MRIs 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are three temporary neuroprotection system, i.e. balloon occlusion 1,3 , filter devices 4,5 , and systems for flow reversal in the internal carotid artery 6 .…”
Section: Introductionmentioning
confidence: 99%